Dominican amber net-winged beetles suggest stable paleoenvironment as a driver for conserved morphology in a paedomorphic lineage - Ferreira, Vinicius S; Solodovnikov, Alexey; Ivie, Michael A; Kundrata, Robin (Scientific reports, 2022)
Paedomorphosis is a heterochronic syndrome in which adult individuals display features of their immature forms. In beetles, this phenomenon occurs widely in the superfamily Elateroidea, including the net-winged beetles (Lycidae), and, due to the usual flightlessness of paedomorphic females, it is hypothesized to cause speciation rates higher than in non-paedomorphic lineages. However, some fossils of paedomorphic lycids do not support this with palaeobiological data. Discovery of new Lycidae fossils attributed to the West Indian extant paedomorphic genus Cessator Kazantsev in the Dominican amber also suggests morphological stasis within this genus in the Greater Antilles. We describe Cessator anachronicus Ferreira and Ivie, sp. nov. based on adult males, as well as the first ever recorded fossil net-winged beetle larva of the same genus. We propose that the relatively young age of the studied fossils combined with the stable conditions in the forest floor of the Greater Antilles through the last tens of million years could explain the exceptionally conserved morphology in the net-winged beetles affected by the paedomorphic syndrome.
Keywords: lesy; brouci; zkameněliny; Female; Dominican Republic; Amber; Animals; jantar; ženské pohlaví; mužské pohlaví; Male; zvířata; Forests; Dominikánská republika; Coleoptera; Fossils